2017
DOI: 10.1007/8904_2017_5
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cellular Homeostasis in Murine MPS I Fibroblasts: Evidence of Cell-Specific Physiopathology

Abstract: Mucopolysaccharidosis type I (MPS I), a rare autosomal recessive disease, is caused by a deficiency of the lysosomal enzyme alfa-L-iduronidase. Impaired enzyme activity promotes glycosaminoglycans accumulation in several tissues and organs, leading to complex multisystemic complications. Several studies using animal models indicated different intracellular pathways involving MPS I physiopathology; however, the exact mechanisms underlying this syndrome are still not understood. Previous results from our group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Contrary to both groups of conclusions mentioned above, normal functions of the autophagy pathway were reported in MPS IIIB (Vitry et al 2010). Accordingly, no alterations in autophagy could be detected in MPS I fibroblasts (Viana et al 2017).…”
Section: Changes In the Autophagy Process In Mps Cellscontrasting
confidence: 74%
“…Contrary to both groups of conclusions mentioned above, normal functions of the autophagy pathway were reported in MPS IIIB (Vitry et al 2010). Accordingly, no alterations in autophagy could be detected in MPS I fibroblasts (Viana et al 2017).…”
Section: Changes In the Autophagy Process In Mps Cellscontrasting
confidence: 74%
“…Storage of undegraded lysosomal substrates severely affects the homeostasis of endo-lysosomal pathway leading to increased size and number of lysosomes, as well as variations in their intracellular position, movement, and docking with other vesicles. It also causes changes in the lipid composition and loss of integrity of the lysosomal membrane and alters expression and activity of lysosomal hydrolases in all affected cells and tissues, including the brain [11,13,16,40,[50][51][52][53][54]. Nondividing cells such as brain neurons use autophagy as the main mechanism for clearance of protein aggregates and damaged organelles [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, defective autophagy has been suggested in MPS II and VII (Bartolomeo et al, 2017; Fiorenza et al, 2018). Contrary to these reports, articles on autophagy in MPS were published, in which the authors suggested either enhancement of this process in MPS I (Woloszynek et al, 2009; Swaroop et al, 2018) or no changes in MPS IIIB (Vitry et al, 2010) and MPS I (Viana et al, 2017). It has been suggested that such opposing conclusions might arise from different interpretation of experimental results.…”
Section: Changes In Cellular Processes and Their Contribution To Pathmentioning
confidence: 99%
“…Interestingly, these findings may explain early observations of structural changes in cells of patients suffering from Sanfilippo disease (MPS III) (Haust, 1968). Recently, lower levels of mitochondrial calcium ions and lower mitochondrial membrane potential were described in MPS I mice relative to control animals (Viana et al, 2017). Interestingly, concentrations of calcium ions were higher in the cytoplasm and endoplasmic reticulum in the same MPS I cells.…”
Section: Changes In Cellular Processes and Their Contribution To Pathmentioning
confidence: 99%